Aklanon Composo as literary text . - Viloria, Janice M. (2006.)
One of the surviving cultural practices in Aklan today is the Aklanon composo. The composo is not popular nowadays and seldom heard, but then a few people still continue to sing them. These songs are simple and since they are called 'folk' they are usually considered less 'poetic' (in a Western sense). then again, in spite of their simplicity adn their being less popular, still they may be considered literary. These songs also have a rhyming pattern and meter. Possessing appropriate symbols, metaphors and images, it is likely possible that these songs really deserve to be studied and be called literary.
Thesis (Undergraduate, Bachelor of Arts in Literature-Psychology) College of Arts and Sciences University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Composo -- Aklan